COVID-19 clinic as a basis of quality primary health care in the light of the pandemic – an observational study - Jurica Ferenčina; Vladimira Tomšič (Medicinski glasnik, 2022)
Aim: The COVID-19 pandemic has had a major impact on societies and has required adjustments of health systems and changes in work processes, especially in the light of an aging population with increased morbidity and mortality. The primary health care level has a key role in maintaining access to healthcare and in addressing the largest proportion of patients with COVID - 19 and should therefore take steps to manage the condition. The aim is to determine the adequacy of COVID-19 clinic model for patients, who are suspected or have a confirmed infection with COVID-19. Methods: In Health Centre Sevnica we have formed a model of the COVID Outpatient Clinic with unlimited access to safe and efficient health care. The introduction of COVID-19 disease diagnostic protocols, regular monitoring of patients, early detection of severe course of the disease and complications have made it possible to treat most patients at the primary health care level without the need for hospitalization. Results: In our COVID clinic in the period 12 March 2020 - 31 January 2021 a total of 22,259 examinations were performed, of which only 284 patients were referred to the hospital level. As expected, the largest share of referrals was in the age group of 65 and over. Conclusion: We believe that the established organization of work represents an optimal solution for managing the COVID-19 pandemic and is also a model with which we can manage future threats.
Keywords: access to health services; general practitioner; health services for aged; SARS CoV2 infection